2015
DOI: 10.1186/s13321-015-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting volume of distribution with decision tree-based regression methods using predicted tissue:plasma partition coefficients

Abstract: BackgroundVolume of distribution is an important pharmacokinetic property that indicates the extent of a drug’s distribution in the body tissues. This paper addresses the problem of how to estimate the apparent volume of distribution at steady state (Vss) of chemical compounds in the human body using decision tree-based regression methods from the area of data mining (or machine learning). Hence, the pros and cons of several different types of decision tree-based regression methods have been discussed. The reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Chemical molecular descriptors are calculated from the chemical structure and are normally used to build predictive models to study the relationship between a compound's chemical structure and its biological and pharmacokinetic properties such as drug distribution and absorption [ 25 , 26 ]. This paper is the first use of chemical molecular descriptors (as well as GO terms) to study the relationship between longevity and the chemical structure of compounds that may affect longevity.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical molecular descriptors are calculated from the chemical structure and are normally used to build predictive models to study the relationship between a compound's chemical structure and its biological and pharmacokinetic properties such as drug distribution and absorption [ 25 , 26 ]. This paper is the first use of chemical molecular descriptors (as well as GO terms) to study the relationship between longevity and the chemical structure of compounds that may affect longevity.…”
Section: Resultsmentioning
confidence: 99%
“…Innovative modeling approaches are needed to understand relationships among data sources of varying complexity and quality and exposure-related factors, processes, and monitoring data. These approaches include machine-learning classification models, which have already proved to be well-suited for pharmacokinetic and hazard-related contexts ( Freitas et al 2015 ; Liu et al 2015 ; Zang et al 2013 ), and agent-based models, which provide a new opportunity to predict exposure-relevant behavior as a function of characteristics of individuals, their environments, and their interactions ( Luke and Stamatakis 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the DT model confirms the other analyses: that CBLI and AirPb are the most important variables in the prediction of OLP. Tree methods became a valuable tool in clinical and in vitro studies but a direct comparison between the predictive models reported is complicated by the differences in the datasets and types of regression methods used [Freitas et al, ].…”
Section: Discussionmentioning
confidence: 99%